Sentimen Analisis dengan Long Short-Term Memory dan Synthetic Minority Over Sampling Technic Pada Aplikasi Digital Perbankan - Ahmad, Ali; Gata, Windu; Panggabean, Supriadi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
In recent years, we have witnessed significant growth in digital banking transactions, supported by technological advancements. According to the latest data from the FinTech Association of Indonesia, digital banking transactions in Indonesia have increased by 35% from the previous year. In this context, the development of digital banking applications becomes increasingly important. However, to ensure the quality and success of these applications, feedback from users is crucial. One technique used by banks is sentiment analysis to gather feedback on their digital applications. This research aims to analyze user sentiment for two banking applications, DbankPro and M-BCA, through reviews on the Google Playstore. The method used is CRISP-DM, implementing the